Contemporary threats to the self-governing nature of local government - Martysz, Czesław (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The political changes in Poland in 1989 also made it possible to reactivate the institutions of local self-government. This occurred in 1990 initially at the commune level, and in 1999 also at the district and voivodeship levels. With the establishment of this self-government, a significant decentralisation of the state took place, as many tasks and competences previously belonging to the state administration were placed within the scope of action of the relevant self-government bodies, in line with the constitutional principle of subsidiarity. In recent years, however, a reverse phenomenon can be observed, consisting in limiting the authority of the self-government, increasing the subjective scope of supervision over the self-government, as well as granting it tasks and competences that could be successfully performed by non-public entities. One can even say that the self-government is treated by the central authorities as a tool to fight the government administration. This is a worrying phenomenon, as the self-government is one of the pillars of the public administration structure.